Fluoroalkyl Amino Reagents (FARs): A General Approach towards the Synthesis of Heterocyclic Compounds Bearing Emergent Fluorinated Substituents - Commare, Bruno (Molecules, 2017)
Fluorinated heterocycles are important building blocks in pharmaceutical, agrochemical and material sciences. Therefore, organofluorine chemistry has witnessed high interest in the development of efficient methods for the introduction of emergent fluorinated substituents (EFS) onto heterocycles. In this context, fluoroalkyl amino reagents (FARs)—a class of chemicals that was slightly forgotten over the last decades—has emerged again recently and proved to be a powerful tool for the introduction of various fluorinated groups onto (hetero)aromatic derivatives.